My 40-Year History with Cronobacter/Enterobacter sakazakii – Lessons Learned, Myths Debunked, and Recommendations - Farmer, John J. (Frontiers in Pediatrics, 2015)
Much has been learned about Cronobacter/Enterobacter sakazakii since I first named and described Enterobacter sakazakii in 1980. However, there are still wide knowledge gaps. One of the most serious is that are still many uncertainties associated with assessing the public health risk from these bacteria, particularly in neonatal meningitis. Over the last few decades Cronobacter contamination of commercial powdered infant formula has apparently been reduced, but it is still an ongoing problem. The powdered infant formula industry still cannot produce powdered formula that is free of bacterial contamination with Cronobacter, other Enterobacteriaceae, and other pathogenic bacteria. Until this happens infants and other will be at risk of becoming infected when contaminated product is ingested.